Caracterização de isolados de Fusarium oxysporum f.sp . lactucae obtidos de campos de produção comercial no Estado de São P aulo e avaliação de genótipos de alface - Frias, Amanda Gretter [UNESP] (2014)
The fusarium wilt, caused b y the soil fungus Fusarium oxysporum f.sp. soil lactucae is one of the most severe diseases that attack lettuce crop worldwide. In 2011, were found in a pla nting lettuce in Capão Bonito and Campinas in São Paulo, symptoms characteristic of this pathogen. S ymptomatic plants were collected for pathogen identification. The optical microscope examinations revealed the presence of hyaline staining falcate macroconidia, microconidia unicellular hyaline and pathogenicity tests revealed the presence of Fusarium oxy sporum f.sp. lactucae. We performed the re - isolation of the pathogen, there by supplementing the Koch's postulate. For this purpose were used: Patriot(susceptible to races 1, 2 and 3), Costa Rica (susceptible to races 2 and 3, resistant to race 1); Summer Green (susceptible to races 1 and 3; resistant to race 2) and Banchu Red Fire (susceptible to races 1 and 3, resistant to race 2). The results show the occurrence of race 3 of Folac. This is the first report of the case in Brazil. From the isolated select ed as being the 3 most aggressive, and characterized as belonging to race 3 was held screening of lettuce genotypes in order to identify sources of resistance for use in breeding programs. From of 63 genotypes tested only Onondaga, Ithaca, Sudenvil and JP - 11 were identified as resistant to race 3 of Fusarium oxysporum f.sp. lactucae